2007
DOI: 10.1007/s10692-007-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase hydrolytic polymerization of caprolactam at 483 K

Abstract: Experimental confirmation of the thermodynamic identity of condensation reactions of amino and carboxyl groups in PCA melt and amorphous phase was obtained. It was shown that the Huggins constant of PCA uniformly increases with an increase in the time the polymer is in the molten state and the moisture content of the melt. The expediency of synthesis of PCA prepolymer in stages with k H ≤ 0.25 for two different values of the moisture content of the melt in a reactor with adjustable water vapor pressure was sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Bazarov proved that CPL hydrolysis polymerization below the melting point of PA6 (210 °C) can effectively reduce the monomer content after equilibrium and recalculated the reaction equilibrium constant according to different water contents. 17 Mizerovskii further studied melt polymerization at a temperature 10−15 °C below the melting point of PA6. 18 Although the molten state can still be maintained at low temperature, it is a metastable state and is not suitable for large-scale application.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bazarov proved that CPL hydrolysis polymerization below the melting point of PA6 (210 °C) can effectively reduce the monomer content after equilibrium and recalculated the reaction equilibrium constant according to different water contents. 17 Mizerovskii further studied melt polymerization at a temperature 10−15 °C below the melting point of PA6. 18 Although the molten state can still be maintained at low temperature, it is a metastable state and is not suitable for large-scale application.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reduction of the reaction temperature is an effective way to control the content of oligomers. Bazarov proved that CPL hydrolysis polymerization below the melting point of PA6 (210 °C) can effectively reduce the monomer content after equilibrium and recalculated the reaction equilibrium constant according to different water contents . Mizerovskii further studied melt polymerization at a temperature 10–15 °C below the melting point of PA6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to water, the production of cyclic oligomers is also affected by the reaction temperature and time. , Therefore, a few studies have reported that the formation of cyclic oligomers can be reduced by adjusting the polymerization process. Bazarov et al opened caprolactam at 210 °C for 8–12 h to obtain the PA6 prepolymer with 6.5–7.0 wt % oligomer and then reduced the monomer and water content by a vacuum method so that the polymerization degree of PA6 reaches 120, and the oligomer content can be reduced to the spinning requirements. Isaeva et al first prepared the PA6 prepolymer from caprolactam, then removed the water in the prepolymer by controlling the pressure, and then placed it in a superheated steam environment for solid-phase polymerization so that the degree of polymerization of the polymer can reach 200, and the oligomer mass fraction is 3.0–4.0%.…”
Section: Introductionmentioning
confidence: 99%